Bibliometric Analysis of The Literature on Science, Technology, Engineering, and Mathematic-Pedagogical Content Knowledge (STEM-PCK) for The Years 2011-202 - Riandi; Santi Hasanah; Ida Kaniawati; Anna Permanasari (Jurnal Inspirasi Pendidikan, 2022)
Analysis of bibliometric literature on Science, Technology, Engineering, and Mathematics (STEM) Pedagogical Content Knowledge spanning 2011-2022. STEM learning is being developed and researched recently. The teacher's role in implementing this learning is very important. Given the importance of the teacher's role in this learning, it is important to analyze research articles to find the relationship between Pedagogical Content Knowledge PCK and STEM, as well as look for opportunities for effective teacher training to improve STEM PCK, science teachers. This research uses the text analysis method, and the data is presented using bibliometric analysis. Searching using the keyword â€œSTEM pedagogical content knowledgeâ€ using publish or perish software, obtained 999 kinds of literature published from 2011 to 2022. From the results of the analysis of PCK and STEM components in the title and abstract using bibliometric analysis, further research opportunities can be obtained by linking the keywords PCK, pedagogical practice, STEM integration, PBL, and student achievement in developing 21st-century skills.